Kalendarium najważniejszych wydarzeń medialnych z historią Łodzi w tle (1821-2006) - Baranek, Katarzyna; Lichawska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
This publication is atypical. It emerged at a quiet place of library and editorial office’s archives.First time the student of the 5th year of Polish philological faculty (library specilization) waspresent at this scientific elaboration. Writing this essay caused a lot of difficulties, not only becauseof a hundred o f old local newspapers that had to be read but the finest selection of the mostimportant medial events. The selection was not easy as all the events seemed to be very importantand worth paying attention. The research area was limited to the media and all what it surroundsand make more valuable, e.g. social communication, culture (movie, theater), science, mass mediaas radio, TV, press or Internet. Discovering of historical events accompanied not only the curiositybut kind of mystery always present at the searching process of activities of our foregrandfathers atthe far past.To invite you to get familiar with that scientific study, we believe that your choice will copeyour expectations.